Die Fragmente der griechischen Historiker. Indexes of parts I, II, and III, Indexes of ancient authors - Jacoby, Felix (Brill, 1999)

Jacoby Die fragmente der griechischen Historiker: indexes of parts I. II, and III ; indexes of ancient authors - Bonnechere, Pierre; Jacoby, Felix (Brill, 1999)
V. 1. Introduction ; Alphabetical list of authors conserving Testimonia & fragments – v. 2. Concordance Jacoby / Source – v. 3. Alphabetical historians with alphabetical list of source-authors for each.
Section: 3 v